2004
DOI: 10.1016/j.jacc.2003.12.046
|View full text |Cite
|
Sign up to set email alerts
|

Hydroquinidine therapy in Brugada syndrome

Abstract: Hydroquinidine therapy prevented VT/VF inducibility in 76% of asymptomatic patients with BrS and inducible arrhythmia, as well as VT/VF recurrence in all BrS patients with multiple ICD shocks. These preliminary data suggest that preventive treatment by HQ may be an alternative strategy to ICD placement in asymptomatic patients with BrS and inducible arrhythmia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(133 citation statements)
references
References 26 publications
7
123
0
3
Order By: Relevance
“…The authors concluded that quinidine effectively suppresses VF induction as well as spontaneous arrhythmias in patients with Brugada syndrome and may be useful as an adjunct to ICD therapy or as an alternative to ICD in cases in which an ICD is refused, unaffordable, or not feasible for any reason. These results are consistent with those reported the same group in prior years (Belhassen et al 1999(Belhassen et al 2002 and more recently by other investigators (Hermida et al 2004;Mok et al 2004). The data highlight the need for randomized clinical trials to assess the effectiveness of quinidine, preferably in patients with frequent events who have already received an ICD.…”
Section: Pharmacologic Approach To Therapysupporting
confidence: 91%
See 1 more Smart Citation
“…The authors concluded that quinidine effectively suppresses VF induction as well as spontaneous arrhythmias in patients with Brugada syndrome and may be useful as an adjunct to ICD therapy or as an alternative to ICD in cases in which an ICD is refused, unaffordable, or not feasible for any reason. These results are consistent with those reported the same group in prior years (Belhassen et al 1999(Belhassen et al 2002 and more recently by other investigators (Hermida et al 2004;Mok et al 2004). The data highlight the need for randomized clinical trials to assess the effectiveness of quinidine, preferably in patients with frequent events who have already received an ICD.…”
Section: Pharmacologic Approach To Therapysupporting
confidence: 91%
“…a Control, BCL 800 ms. b Terfenadine (5 μM) induces ST segment elevation as a result of heterogeneous loss of the epicardial action potential dome, leading to phase 2 reentry3 which triggers a closely coupled extrasystole (BCL = 800 ms). c Addition of AVEO 118 (7 μM) prevents loss of the epicardial action potential dome and phase 2 reentry-induced arrhythmias (BCL = 800 ms) Table 2 Device nad pharmacologic apaproach to therapy of the Brugada syndrome Devices and Ablation ICD (Brugada et al 2000a) ?Ablation or Cryosurgery (Haissaguerre et l. 2003) ?Pacemaker (vn den Berg et al 2001) Pharmcaologic Approach to Therapy Ineffective Amiodarone β-Blockers (Brugadaa et al 1998) Class iC antiarrhythmics Flecainide (Shimizu et al 2000a) Propafenone (Matana et al 2000) ?Disopyramide (Chinushi et al 1997) Class IA aaantiarrhythmics Procainaamide (Brugada et al 2000c) Effective for treatment of electrical storms β-Adrenergic agonists-isoproterenol (Miyazaki et al 1996;Shihmizu et al 2000b) Phosphodiesterase III inhibitors-cilostazol (Tsuchiya et al 2002) Effective general therapy Class IA antiarrythmics Quinidine (Belhassen and Viskin 2004;Alings et al 2001;Belhassen et al 1999Belhassen et al , 2002Yan and Antzelevitch 1999;Hermida et al 2004;Mok et al 2004) Experimental therapy I to blockers-cardioselective and ion channel specific Quinidine (Yan and Antzelevitch 1999) 4-Aaminopyridine (Yan and Antzelevitch 1999) Tedisamil (Fish et al 2004b) AVE0118 (Fish et al 2004a) …”
Section: Pharmacologic Approach To Therapymentioning
confidence: 99%
“…12) A number of reports have shown the effectiveness of quinidine in treatment of Brugada syndrome. [13][14][15][16][17][18][19] Because the typical features of Brugada syndrome were not observed in this case, it is unclear whether quinidine would have been effective. If VF storms occur despite the administration of quinidine, we are considering EPS and ablation under alcohol administration.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they both respond well to quinidine, isoproterenol and cilostazol, explained by the effect of these agents on inhibition of potassium currents or increase of calcium currents. 37 Apart from the similar ECG and clinical phenotype, some differences can be also appreciated between the two entities. They include: …”
Section: Overlapping Features Of Brugada and Early Repolarisation Synmentioning
confidence: 99%